Designing formative assessment lessons for concept development and problem solving - Swan, Malcolm (2015)
Formative assessment is the process by which teachers and students gather evidence of learning and then use this to adapt the way they teach and learn. I describe a design research project in which we integrated formative assessment strategies into lesson materials that focus on developing students’ conceptual understanding and their capacity to tackle non-routine problems. A theoretical framework for assessment task design is presented, together with an analysis of research-based principles for formative assessment lesson design. Particular aspects are highlighted: the roles of pre-assessment, formative feedback questions and sample work for students to critique. While there are some early signs that these lessons provide an effective model for teachers to introduce formative assessment into everyday classroom practice, the materials require a radical shift in the predominant culture within most classrooms.